Respuesta :

If you factor that out, it would be 4(x+6)(x+3)

Answer:

Factorization of [tex]4x^2 + 36x + 72[/tex] is:

4(x+3)(x+6)

factors are: 4, x+3 and x+6

Step-by-step explanation:

we are given a expression:

[tex]4x^2 + 36x + 72[/tex]

We have to factorize this expression

[tex]4x^2 + 36x + 72=4(x^2+9x+18)[/tex]

Now, we factorize [tex](x^2+9x+18)[/tex]

[tex]x^2+9x+18=x^2+6x+3x+18\\\\=x(x+6)+3(x+6)\\\\=(x+3)(x+6)[/tex]

Hence, factorization of [tex]4x^2 + 36x + 72[/tex] is:

4(x+3)(x+6)

factors are: 4, x+3 and x+6